Creating the Curriculum. - Wyse, Dominic (Understanding primary education series., 2012)
Is there an 'ideal' primary school curriculum?Who should decide what the curriculum is?Should teachers have autonomy over how they teach?The curriculum is the heart of what teachers teach and learners learn: effective teaching is only possible with an effective curriculum. Yet in spite of its importance, there has been a crisis in curriculum that has been caused in large part by governments assuming direct control over the curriculum, assessment, and increasingly, pedagogy. Creating the Curriculum tackles this thorny issue head on, challenging student and practising primary school teachers to.